2011
DOI: 10.1177/0269215511403941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of home-based exercise training for patients with chronic heart failure and sleep apnoea: a randomized comparison of two different programmes

Abstract: Home-based exercise training is an important therapeutic strategy in chronic heart failure patients with sleep apnoea, and strength training resulted in a higher increase in muscle strength and endurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(103 citation statements)
references
References 28 publications
4
91
2
3
Order By: Relevance
“…In addition, we found no significant difference in knee extension strength or resistance after 3 months of HB or CB training. This is consistent with previous studies [35,36]. Conraads et al, collected muscle strength data in 75 CAD patients before and after 12 weeks of an AIT or ACT CR program finding that muscle strength did not improve.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, we found no significant difference in knee extension strength or resistance after 3 months of HB or CB training. This is consistent with previous studies [35,36]. Conraads et al, collected muscle strength data in 75 CAD patients before and after 12 weeks of an AIT or ACT CR program finding that muscle strength did not improve.…”
Section: Discussionsupporting
confidence: 92%
“…Factors contributing to this discrepancy remain unclear. However, an overall 30% drop-out rate was observed in one study (Oka et al, 2000), compared to 10% in another study (Servantes et al, 2011). Studies which compared telerehabilitation and centre-based exercise, found no significant difference in VO2peak between groups of patients with cardiac conditions (Arthur et al, 2002;Piotrowicz et al, 2010).…”
Section: Vo2peakmentioning
confidence: 96%
“…Two studies found no significant difference in post-program VO2peak between telerehabilitation and no intervention in patients with cardiac conditions (see Figure 2-3) (Brubaker et al, 2000;Oka et al, 2000). Conversely, some studies found a significant improvement in VO2peak following telerehabilitation for patients with cardiac conditions, whereas no intervention group showed a decline (Salvetti et al, 2008;Servantes et al, 2011). Factors contributing to this discrepancy remain unclear.…”
Section: Vo2peakmentioning
confidence: 99%
See 2 more Smart Citations